Efficient implementation of the Hodgkin-Huxley potassium channel via a single volatile memristor - Lennart P. L. Landsmeer; Lennart P. L. Landsmeer; Erbing Hua; Heba Abunahla; Muhammad Ali Siddiqi; Muhammad Ali Siddiqi; Muhammad Ali Siddiqi; Ryoichi Ishihara; Chris I. De Zeeuw; Chris I. De Zeeuw; Said Hamdioui; Christos Strydis; et al. (Frontiers in Neuroscience, 2025)
IntroductionIn 2012, potassium and sodium ion channels in Hodgkin-Huxley-based brain models were shown to exhibit memristive behavior. This positioned memristors as strong candidates for implementing biologically accurate artificial neurons. Memristor-based brain simulations offer advantages in energy efficiency, scalability, and compactness, benefiting fields such as soft robotics, embedded systems, and neuroprosthetics.MethodsPrevious approaches used current-controlled Mott memristors, which poorly matched the voltage-controlled nature of ion channels. This study employs volatile, oxide-based memristors that leverage electric-field-driven oxygen-vacancy migration to emulate voltage-dependent channel behavior. We selected candidate WOx and NbOx memristors and modeled their dynamics to verify performance as Hodgkin-Huxley potassium channels.ResultsThe device exhibits sigmoidal gating and voltage-dependent time constants consistent with the theoretical model. By scaling the passive circuitry around the memristors, we show that they capture the essential mechanisms of potassium ion-channels, although spike height is reduced due to strong non-linear voltage-dependence. Still, by cascading multiple compartments, typical spike propagation is retained.DiscussionThis is the first demonstration of a voltage-controlled memristor replicating the Hodgkin-Huxley potassium channel, validating its potential for more efficient brain simulation hardware.